Boerhaave's syndrome: a case with an atypical right-sided oesophageal perforation - Sjekavica, Ivica (Radiology and oncology (Ljubljana), 2004)
Background. Boerhaave's syndrome is a complete transmural perforation of the thoracic oesophagus, with the oesophageal tear occurring on the left posterolateral side in 90% of the patients. Case report. We present a case of Boerhaave's syndrome with an atypical feature of right-sided oesophageal rupture. Chest CT has the advantage of imaging all thoracic structures and complications and excluding differentially diagnostic conditions in the case of a high clinical suspicion of oesophageal rupture. Conclusions. CT is especially important in patients whose severe clinical condition does not permit esophagography.
Keywords: diagnostika; Esophageal Diseases; Middle Age; požiralnik; Požiralnik, bolezni; ruptura; Ruptura spontana; Rupture, Spontaneous; Srednja leta; tomografija; Tomografija radiografska, računalniška; Tomography, X-Ray Computed